STRATEGI GURU DALAM MENINGKATKAN MINAT MEMBACA MELALUI PEMBELAJARAN BAHASA INDONESIA DI MA JA’AL-HAQ KOTA BENGKULU - Septiani, Neni; Heriadi, Meddyan; Yumarni, Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading interest is one of the fundamental aspects of developing students’ literacy skills, particularly in Indonesian language learning. However, the low level of reading interest among students remains a challenge faced by many educational institutions. This study aims to describe teachers’ strategies in enhancing students’ reading interest through Indonesian language learning. The research employed a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews with teachers and students, and documentation of learning activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that teachers implement various strategies to foster students’ reading interest, including the use of reading materials relevant to students’ needs and interests, the application of interactive teaching methods, the utilization of digital media, the development of school literacy programs, and the provision of motivation and appreciation for reading activities. In addition, teachers play a role as facilitators by creating a conducive learning environment that supports a culture of literacy. These strategies have proven effective in increasing students’ enthusiasm for reading, broadening their knowledge, and developing critical thinking and language skills. Therefore, the role of teachers in designing and implementing innovative learning strategies is a crucial factor in improving students’ reading interest through Indonesian language learning.